Exploring the Issue of Failure to Fail in Professional Education Programs: A Multidisciplinary Study - Luhanga, Florence; Larocque, Sylvie; MacEwan, Leigh; Gwekwerere, Yovita; Danyluk, Patricia (Journal of University Teaching and Learning Practice, 2014)
There is a universal demand for well-prepared professionals in all disciplines, and society has entrusted professional schools with the task of preparing such individuals (Ralph, Walker, and Wimmer, 2008). Within this context, field or clinical instructors and university faculty have an academic and professional responsibility to teach, supervise, and evaluate students’ field or clinical experience to ensure that each graduate of their program is competent. However, there is evidence that some instructors and university faculty experience difficulty in identifying and making decisions to fail students who display incompetent or unsatisfactory practice (Bogo, Regehr, Power, and Regehr, 2007; Brown, Neudorf, Poitras, and Rodgers, 2007; Hawe, 2003). A qualitative descriptive design was used to explore the issue of “failure to fail” in professional programs including Nursing, Education, and Social Work. Results indicate that: (a) failing a student is a difficult process; (b) both academic and emotional support are required for students and field instructors/preceptors/ faculty advisors; (c) there are consequences for programs, faculty, and students when a student has failed a placement; (d) at times, personal, professional, and structural reasons exist for failing to fail a student; and (e) the reputation of the professional program can be diminished as a result of failing to fail a student. Recommendations for improving the quality of field or clinical experiences and support for students and field instructors/preceptors and will thus improve the quality of our programs and graduates are presented.